Pengaruh game warming up terhadap motivasi belajar bola voli - Falah, Cahyandi; Abduloh, Abduloh; Irawan, Astri Ayu (Universitas Hamzanwadi, 2023)
The problem is that students don't have motivation in learning physical education, especially in volleyball material. The purpose of this study was to determine the effect of a warming up game in increasing motivation to learn volleyball. This research method is quantitative experiment. The population in this study were students of class X in the pharmacy department, totaling 43 female students. The data in this study were taken with a one group pretest posttest design for six meetings. The research instrument used a learning motivation questionnaire and data collection techniques with a Likert scale. Data analysis was carried out by testing the validity, reliability, normality test, homogeneity test, and paired sample t test. The average result at the pretest was 63.5 and the average result at the posttest was 81.9. The results of t count -27,818 > t table 2,018. The magnitude of the influence is 29%. So it can be concluded that there is a significant influence on the motivation to learn volleyball through the warming up game.